Digital health systems: SMART-system for remote support of hybrid E-rehabilitation services and activities - Palagin, O.V.; Malakhov, K.S.; Velychko, V.Yu.; Semykopna, T.V.; Shchurov, O.S. (Проблеми програмування, 2022)
The top-priority challenges were faced by the medical rehabilitation system in Ukraine. Particularly important tasks include, first of all, the rehabilitation of patients who have recovered from COVID-19 disease and people with Combat stress reaction. This fact is well understood both by the society and the leadership of the Ministry of Health of Ukraine, which is creating a special working group on this problem. Ukraine has a system of medical and prophylactic institutions designed for psychological and physical rehabilitation of military personnel; these use modern rehabilitation technologies. However, long-term rehabilitation in such centers is not available to everyone. Therefore, the use of telerehabilitation technology for patients with post-traumatic stress disorder and similar disorders in combination with a means of objective control of the functional state is extremely important. One of the most effective solutions in medical rehabilitation assistance is remote patient / person-centered rehabilitation. Rehabilitation also needs effective methods for the "Physical therapist – Patient – Multidisciplinary team" system, including the statistical processing of large volumes of data. Therefore, along with the traditional means of rehabilitation, as part of the "Transdisciplinary intelligent information and analytical system for the rehabilitation processes support in a pandemic (TISP)" in this paper, we introduce and define: the revised and completed basic concepts of the hybrid e-rehabilitation notion and its fundamental foundations; the formalization concept of the new Smart-system for remote support of hybrid e-rehabilitation services and activities; and the methodological foundations for the use of services (UkrVectōrēs and vHealth) of the remote Patient / Personcentered Smart-system. The software implementation of the services of the Smart-system has been developed. Першочергові виклики постали перед системою охорони здоров’я та медичної реабілітації в Україні. До особливо важливих завдань відноситься, у першу чергу, реабілітація хворих, які одужали від COVID-19 та людей з бойовою психічною травмою. Цей факт добре усвідомлюється, як суспільством, так і керівництвом МОЗ України, яке наразі створює спеціальну робочу групу з цієї проблеми. Україна має систему лікувально-профілактичних закладів, призначених для психологічної та фізичної реабілітації військовослужбовців, в яких використовуються сучасні технології реабілітації. Однак, довготривала реабілітація в таких центрах доступна далеко не всім. Тому, застосування технології телереабілітації хворих з посттравматичним стресовим розладом та подібними розладами, в поєднанні з засобами об’єктивного контролю функціонального стану є вкрай важливим. Одним з ефективних рішень в наданні медичної реабілітаційної допомоги є дистанційна пацієнт-центрична реабілітація – гібридна е-реабілітація, яка потребує online-засобів теледіагностики, телеметрії і втручання з орієнтацією на можливості пацієнта, розвинутої Internet-взаємодії, інтелектуальних інформаційних технологій і сервісів, ефективних методів когнітивної підтримки в системі "Реабілітолог – Пацієнт – Мультидисциплінарна команда", статистичної обробки великих об’ємів інформації тощо. Звідси поряд з традиційними засобами реабілітації у складі системи Трансдисциплінарної інтелектуальної інформаційно-аналітичної системи супроводження процесів реабілітації при пандемії TISP з’явилася Smart-система телемедичного супроводження гібридних е-реабілітаційних заходів. Розроблено формальну модель, програмну реалізацію та методологічні засади застосування сервісів (UkrVectōrēs та vHealth) дистанційної пацієнт-центричної Smart-системи надання медичної реабілітаційної допомоги.